Process dynamic and control for nonconventional column/rectifier configuration with aspen hysys v10.0 - Hikmadiyar, R. A.; Sutikno, Juwari P.; Handogo, R.; Azizah, Z.; Anwaruddin, Hisyam (IOP Publishing, 2019)
Nonconventional column/rectifier configuration is the new alternate design for the sequence multicomponent separation of three or more products. It can accomplish an efficient energy. There are two columns, the first is the rectifier and the second is the main, the vapor sidestream is taken out from the location under the feed tray of the main column then fed to the rectifier column and the liquid that from the bottom of the rectifier column is turned back to the main column. In order to completely understand the dynamic behavior of complex process of this configuration, process dynamic and control of it has to be studied intensively. The implementation of it is demethanizer and deethanizer column. The configuration has been simulated for dynamic by using Aspen Hysys v10.0. The results show that the graph of rejecting disturbance from all controllers of the main column need more attention especially for inventory control i.e. level controller for reflux drum, sump level reboiler and pressure controller for condenser. The overshoot for level controller of reflux drum of main column is 10% from set points. The better algorithm of tuning is required. The results of this studied could provide guidance for composition controller of this configuration.